Determination of crosslink densities of filled rubbers by cyclic pre-straining - Faridah H A H; Farid A S; Tinker A J (Journal of Rubber Research, 2004)
Physically effective crosslink densities are determined for gum, calcium cabonate-filled and carbon black-filled vulcanisates by using cyclic pre-straining (scragging) prior to stress-strain measurements to obtain the Mooney-Rivlin constant, C1. The procedure was shown to be valid for natural rubber (NR) vulcanisates. Calcium cabonate was found not to interfere in sulphur vulcanisation, whereas carbon black increased the yield of crosslinks. The scragged C1 procedure was not applicable to high acronitrile (41;)-butadiene rubber (NBR) due to difficulties ascribed to hysteresial effects arising from the relatively high glass-transition temperature (Tg) of the rubber. For gum NBR vulcanisates, crosslink densities were overe-stimated by about 13;. The procedure gave extremely low estimates of crosslink density for calcium carbonate-filled NBR vulcanisates, but some emperical relationships provided estimates that were in excellent accord with the values for comparable gum vulcanisates. Crosslink densities for black-filled NBR vulcanisates were determined by equilibrium swelling, with appropriate corrections for swelling restriction by the carbon black, and comparison with values determined from scragged C1 measurements showed the latter to be about 10;higher. Again, carbon black increased the yield of crosslinks.
Keywords: Calcium carbonate; Carbon black; Crosslink; Cyclic; Density; Determination; Filled rubbers; Gum; NBR; NR; Pre-straining; Scragging; Vulcanisates